On Improving Indoor Navigation Accuracy Using Bluetooth Beacons - Rattapon Kaewpinjai (2020)
© 2020 IEEE. In this paper, we propose a navigation assistive event management platform. This platform presents a novel approach for organizing an exhibition by allowing both organizers and visitors to interact together in a real-time manner. The platform also provides location-based services. The location of the visitors is calculated using multilateration technique with the help of available WiFi signals in the building. Additionally, in order to improve localization accuracy, several Bluetooth beacons were introduced. It has been shown from the experiments that Blue-tooth beacon deployment can significantly i mprove localization precision. Several empirical pathloss models for both WiFi and Bluetooth signals defined u nder a r eal-world e nvironment were proposed and compared in this paper.